TYPES AND CLASSIFICATIONS OF PHRASEOLOGICAL UNITS IN LANGUAGE STUDIES (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Phraseological fusions in phraseological combinations the level of inspiration is extremely low, we can't figure the significance of the entire from the implications of its parts, they are profoundly informal and can't be translated into the same words in different languages, e.g. to test one's sanity (to mislead); perplexed (in disarray); a female horse's home ( a revelation which ends up being bogus or useless); to show the white quill (to show weakness); to ride the lofty self-esteem (to grandstand). Phraseological combinations are the most informal of the multitude of sorts of phraseological units.